Exploring the relationship between aural decoding and listening comprehension among L2 learners of English. (February 2022) - Ke, Zhangxuan; Wang, Yun
Abstract: Research on second language (L2) learners' aural decoding, a bottom-up process in listening comprehension, has not been given enough attention. To help researchers and teachers understand the aural decoding processing, this study investigates the relationship between aural decoding and L2 listening comprehension involving 42 second-year students majoring in English in a Chinese university. Findings indicate that: 1) there was a strong correlation between aural decoding and L2 listening comprehension ( r = 0.69, p < .01); 2) a threshold of aural decoding of around 80% of decoding scores may lead to good L2 listening comprehension; 3) aural decoding scores may predict 46.9% of the variance in L2 listening comprehension. Additionally, results show that the most frequent decoding errors tend to be those which have no similarities to the input and those which are phonetically similar to the input. The most common reason leading to such errors seems to be that learners encountered words they had never heard before. Implications for pedagogical practice in L2 classrooms are discussed.